2016
DOI: 10.1037/emo0000192
|View full text |Cite
|
Sign up to set email alerts
|

Recognition thresholds for static and dynamic emotional faces.

Abstract: We investigated the minimum expressive intensity that is required to recognize (above chance) static and dynamic facial expressions of happiness, sadness, anger, disgust, fear, and surprise. To this end, we varied the degree of intensity of emotional expressions unfolding from a neutral face, by means of graphics morphing software. The resulting face stimuli (photographs and short videos) were presented in an expression categorization task for 1 s each, and measures of sensitivity or discrimination (A') were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 71 publications
4
64
1
1
Order By: Relevance
“…36 Problems in the area of coverage of the study and the sample was similar to that found in other studies involving older adults with depression. [11][12][13] Finally, the presence of individuals with comorbid anxiety disorders in the group with depression may have exerted an influence on the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Problems in the area of coverage of the study and the sample was similar to that found in other studies involving older adults with depression. [11][12][13] Finally, the presence of individuals with comorbid anxiety disorders in the group with depression may have exerted an influence on the results.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, despite evidence of the relationship between one's performance on facial emotion recognition tasks and depression, few studies have evaluated this relationship in older adults. [11][12][13] Moreover, all studies on facial emotion recognition in older adults with depression published to date have used tasks with static stimuli only. Therefore, this study is the first to use tasks with dynamic stimuli to evaluate facial emotion recognition in older adults with depression, and the findings may have implications for clinical practice, as the ability of facial emotion recognition is a possible predictor of response to antidepressants in older adults with depression.…”
Section: Resultsmentioning
confidence: 99%
“…For example a review by Nelson and Russell (2013) , concluded that happiness is the emotion with the highest percentage of hits (around 90%) across cultures and languages. Indeed, the identification threshold for a happy expression is particularly low, given that this emotion can be recognized even when presented very fast (e.g., Calvo and Lundqvist, 2008 ) and with minimal intensity ( Calvo et al, 2016 ). Moreover, happy faces not only were perceived as the most positive and familiar (e.g., Garrido et al, 2016 ), but also as the most attractive (e.g., Golle et al, 2014 ; Garrido et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recio et al (2014) found that the recognition accuracy of all six basic expressions was above 70% (except fear: 62.5%) already at a 60% intensity level. In a recent study (Calvo, Avero, Fernández-Martín, & Recio, 2015), intensity levels were morphed from 20% to 100%. Measures of discrimination (A') established recognition thresholds: 20% of intensity for happiness; 40% for sadness, surprise, anger and disgust; 50-60% for fear, similarly for dynamic and static expressions.…”
Section: Recognition Of Facial Expressions Cognition and Emotion 2015mentioning
confidence: 98%